Functional neuroanatomy of response inhibition in bipolar disorders--combined voxel based and cognitive performance meta-analysis - Hajek, Tomas; Alda, Martin; Hajek, Eva; Ivanoff, Jason (Journal of psychiatric research, 2013)
OBJECTIVES: Impaired response inhibition underlies symptoms and altered functioning in patients with bipolar disorders (BD). The interpretation of fMRI studies requires an accurate estimation of neurocognitive performance, for which individual studies are typically underpowered. Thus, we performed the first combined meta-analysis of fMRI activations and neurocognitive performance in studies investigating response inhibition in BD. METHODS: We used signed differential mapping to combine anatomical coordinates of activation and standardized differences between means to evaluate neurocognitive performance in 30 fMRI studies of response inhibition comparing controls (n = 667) and patients with BD (n = 635). RESULTS: Relative to controls, BD patients underactivated the right inferior frontal gyrus (rIFG) regardless of current mood state and behavioral performance. Unique to euthymia were cortical hyperactivations (left superior temporal, right middle frontal gyri) combined with subcortical hypoactivations (basal ganglia), whereas unique to mania were subcortical hyperactivations (bilateral basal ganglia), combined with cortical hypoactivations (right inferior and medial frontal gyri). The fMRI changes in euthymia were associated with normal cognitive performance, whereas manic patients committed more errors during response inhibition. CONCLUSIONS: The rIFG hypoactivations were congruent with a BD trait, which may underlie the impaired response inhibition in mania. Euthymic BD subjects may compensate for the rIFG hypoactivations by hyperactivations of adjacent cortical areas, yielding comparable performance in inhibitory functions and suggesting possibilities for neuromodulation treatment of these cognitive impairments. The reversal of the activation pattern between mania and euthymia has implications for monitoring of treatment response and identification of imminent relapse.
Keywords: databáze bibliografické; fMRI; počítačové zpracování obrazu; bipolární porucha; Cognition Disorders; mužské pohlaví; Databases, Bibliographic; Bipolar Disorder; inhibice (psychologie); kognitivní poruchy; magnetická rezonanční tomografie; Magnetic Resonance Imaging; kyslík; ženské pohlaví; Response inhibition; Humans; Inferior frontal gyrus; Bipolar disorders; Frontal Lobe; Image Processing, Computer-Assisted; Oxygen; Female; čelní lalok; Inhibition, Psychological; lidé; Male